(untitled) (Asian Journal of Medical and Biological Research, 2024)
Effective preventive methods for suicide need a thorough understanding of the risk factors associated with this complex and varied public health issue. This research aims to explore instances of suicide as documented in Bangladeshi newspapers, specifically examining distinctive risk factors associated with gender and demographics. 13 national daily newspapers were selected purposively data in this investigation. The logistic regression method was used for analysis and fitting to the dataset. Higher suicide odds among individuals under 30 and employed individuals. Significant regional differences are noted, with Khulna having a rate of 1.05 (OR=1.05, 95% CI: [0.45-1.42]) and Chittagong the lowest at 76% (OR=0.24, 95% CI: [0.18-0.41]) compared to Sylhet. Certain methods like hanging, poisoning, and jumping show elevated odds 1.75 (95% CI: [1.51-1.86]), 1.83 (95% CI: [0.79-1.98]), and 1.72 (95% CI: [1.53-1.97]), respectively, compared to self-harm methods among women, while factors like family issues and blackmail exhibit significantly higher odds 2.82 (95% CI: [1.85-3.10]), 1.01 (95% CI: [0.89-1.12]), and 2.06 (95% CI: [1.99-2.15]), respectively, compared to physical illness among women. By elucidating the intricacies associated with suicide risk factors in Bangladesh, our study adds to the international conversation on suicide prevention by promoting a more sophisticated comprehension of gender differences to augment the efficacy of public health campaigns. Asian J. Med. Biol. Res. 2024, 10(3), 110-118